Care visits: obligations, opportunities and constraints for Vietnamese grandparent visitors in Australia. Issue 4 (25th February 2023) - Thi Nguyen, Hien; Baldassar, Loretta; Wilding, Raelene
ABSTRACT: In examining the ageing-migration nexus from a Global South perspective, this paper explores the obligations, opportunities and constraints of caregiving performed by Vietnamese grandparent visitors during their sojourns in Australia. Employing a grounded theory approach and care circulation framework, we investigate how grandparent visitors and adult migrant children experience and understand care and ageing in contexts of mobility, including an analysis of how gender, age, socio-economic contexts and culture shape and affect their care norms and practices. The analysis emphasizes the critical contributions that Vietnamese grandparents make to the reproductive labour of their adult migrant children who often face challenges in balancing their family and work life. The resultant 'informal unpaid care mobility' of Vietnamese grandparents visitors creates 'informal care chains' that underscore the role of mobility as a care resource and the need for unpaid family care in migrant families due to the high cost of formal childcare in Australia. This analysis extends our understanding of the political economy of care, by highlighting the need for greater analysis of South–North informal care flows.